2007
DOI: 10.1111/j.1365-2893.2007.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR7 single nucleotide polymorphisms with chronic HCV‐infection and response to interferon‐a‐based therapy

Abstract: An efficient immune response against hepatitis C virus (HCV) is necessary to clear infection. As HCV is a single-stranded RNA virus, a role for TLR7 in the immune response against HCV is possible, and early clinical studies have demonstrated an antiviral effect of TLR7 stimulation. We tested the hypothesis that genetic variations of TLR7 are associated with chronic HCV-infection and outcome of therapy. The prevalence of three TLR7 variations was analysed in 978 patients with chronic HCV-infection, 898 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 43 publications
(65 reference statements)
1
51
0
1
Order By: Relevance
“…These are the only reported effects of the SNP at the protein/cellular level and these data were mostly (for livers), or completely (for pDCs), derived from hemizygous males. As stated above, however, most reported clinical effects of the SNP are observed in females (Oh et al, 2009;Schott et al, 2007b). We also identified effects of the SNP only in females.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These are the only reported effects of the SNP at the protein/cellular level and these data were mostly (for livers), or completely (for pDCs), derived from hemizygous males. As stated above, however, most reported clinical effects of the SNP are observed in females (Oh et al, 2009;Schott et al, 2007b). We also identified effects of the SNP only in females.…”
Section: Discussionmentioning
confidence: 67%
“…In both infections, the variant allele associated with higher disease prevalence and augmented disease progression, and with reduced response to IFNα-therapy for HCV (Oh et al, 2009;Said et al, 2014;Askar et al, 2010;Schott et al, 2007b;Fakhir et al, 2018). In all these studies, effects were most prominent in (mostly rs179008 heterozygous) females and all studies predominantly contained Caucasian individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Variations in TLR7 and some ISGs have been shown to be associated with HCV infection outcome (reviewed in (Rauch, Gaudieri et al 2009). One such study has shown the association between variations within TLR 7 and HCV infection outcome (Schott, Witt et al 2008). In this study, variants at position 32 and 2403 of TLR7 were associated with viral persistence and IFN- treatment outcome.…”
Section: Host Genetic Diversity and Natural History Of Hcv Infectionmentioning
confidence: 81%
“…Underlined HLA alleles appear in more than one study. References: (Thio, Gao et al 2002;McKiernan, Hagan et al 2004;Wang, Zheng et al 2009), (Thio, Thomas et al 2001;Yee 2004;Yoon, Han et al 2005;Ksiaa, Ayed-Jendoubi et al 2007;Harris, Sugimoto et al 2008), (Ishida, Ikebuchi et al 2011), (Falleti, Fabris et al 2010), (Haas, Weiß et al 2009), (Mueller, Mas-Marques et al 2004), (Yee, Tang et al 2001) (Morgan, Lambrecht et al 2008), (Thio, Goedert et al 2004;Paladino, Fainboim et al 2006), (Knapp, Hennig et al 2003;Lio, Caruso et al 2003;Kimura, Saito et al 2006;An, Thio et al 2008), (Schott, Witt et al 2008), (Huang, Yang et al 2007), (Ge, Fellay et al 2009;Mangia, Thompson et al 2010), (Tanaka, Nishida et al 2009;Rauch, Kutalik et al 2010), (Vejbaesya, Nonnoi et al 2011), (Khakoo, Thio et al 2004;Montes-Cano, Caro-Oleas et al 2005), (Persico, Capasso et al 2008), (Su, Yee et al 2008), (Suzuki, Arase et al 2004), (Knapp, Yee et al 2003), (Dai, Chuang et al 2010). The innate immune system has a critical role in detecting pathogens and triggering the immune response.…”
Section: Host Genetic Diversity and Natural History Of Hcv Infectionmentioning
confidence: 99%
“…For instance, the c.32A > T variation in TLR7 was over-represented in female patients with chronic HCV infection compared to patients with other chronic liver diseases and healthy controls, and its presence had a predictive value of an unfavorable outcome of IFN-a therapy, suggesting that variations of TLR7 alter the immune response to HCV infection (Schott 2008). Likewise, polymorphisms in TLR7 and TLR8 have been linked to susceptibility to HCV infection in the Taiwanese population (Wang and others 2011).…”
Section: Snps In Other Tlrsmentioning
confidence: 99%